Would Mexican Migrants be Willing to Guarantee Americans a Basic Income? - Lokshin, Michael; Ravallion, Martin (World Bank, Washington, DC, 2021)
The paper simulates a double-sided competitive market in temporary work permits between the U.S. and Mexico. Eligible working-age Americans would have the option of renting out their implicit work permits while Mexican workers have remunerative new opportunities. With plausible allowances for migration costs, the market can support a self-financed and self-targeted basic income for Americans and lower their poverty rate. With sufficiently high tax rates on work permits, the scheme can be managed to avoid a large increase in the count of total migrants compared to now. The likely change in the skill composition of migrants would raise U.S. GDP.